Assessment on the condition of school facilities: case study of the selected public schools in Gombak district - Mohd Ibrahim, Nuraihan; Mohamed Osman, Mariana; Bachok, Syahriah; Mohamed, Mohd Zin (Elsevier, 2016)
Parents’ criteria for selecting the suitable school were influenced by the facilities provided by the school. The objectives of the paper is to examine the requirements and planning standards and guidelines of public schools development, to assess the condition of the school facilities in the study area, and to provide the recommendations to improve the development of public schools. The site observations were carried out to provide a clear view of the school components and the school surroundings. The data gathered from the site observation is recorded using inventory lists. The recommendations were proposed to improve the condition of the school facilities.